An Anthropology of Landscape (2017)
An Anthropology of Landscape tells the fascinating story of a heathland landscape in south-west England and the way different individuals and groups engage with it. Based on a long-term anthropological study, the book emphasises four individual themes: embodied identities, the landscape as a sensuous material form that is acted upon and in turn acts on people, the landscape as contested, and its relation to emotion. The landscape is discussed in relation to these themes as both ‘taskscape’ and ‘leisurescape’, and from the perspective of different user groups. First, those who manage the landscape and use it for work: conservationists, environmentalists, archaeologists, the Royal Marines, and quarrying interests. Second, those who use it in their leisure time: cyclists and horse riders, model aircraft flyers, walkers, people who fish there, and artists who are inspired by it. The book makes an innovative contribution to landscape studies and will appeal to all those interested in nature conservation, historic preservation, the politics of nature, the politics of identity, and an anthropology of Britain.UCL Press